The molecular function of class A and B carbapenemase genes in the antibiotic resistance of Klebsilla pneumoniae isolated from urinary tract infection - A. H. Najim; W. A. Ghrabi (Regulatory Mechanisms in Biosystems, 2025)
Today, some of the β-lactamase enzymes that can render the last class of carbapenems inactive are the carbapenemase e n zymes, which are derived from the bacterium Klebsiella pneumoniae . The purpose of this work is to identify and assess KPC and NDM-I gene expression in local isolates of K. pneumonia e using real-time PCR. In Baghdad City, Iraq, urine samples from patients with UTIs at Al-Yarmouk General Hospital and Al-Karama General Hospital yielded 150 K. pneumonia e isolates. Fo l lowing cultivation on nutritional agar and MacConkey agar medium, K. pneumonia e was identified and the carbapenemase gene was detected using PCR. The presence of the K. pneumoniae 16S rRNA gene (95 bp), a gene used to identify K. pneumoniae , was detected molecularly using the polymerase chain reaction (PCR) for each extracted DNA sample. Specific primers were utilized. The findings of the traditional PCR method demonstrated that 20 (100%) of the 20 isolates of K. pneumoniae that were resistant to carbapenem carried the KPC gene, which has a size of 221 bp. These data show that our local isolates are resistant to carbapenem, which is associated with the production of the KPC gene. Twenty (100%) of the 20 carbapenem-resistant K. pne u moniae isolates were found to have the NDM1 gene (131 bp) . Furthermore, in Real-Time PCR, all isolates treated with cranberry and bearberry herbal extracts exhibited down expression of the KPC and NDM1 genes in comparison to the housekeeping gene when compared to the control. Based on these fin dings, it can be concluded that the carbapenem-resistant isolates were members of the current class A and B genes, which are highly expressed in our local isolates.